2016
DOI: 10.5433/1679-0359.2016v37n5p3277
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of beef cattle grazing Brachiariabrizantha during the dry and rainy seasons: performance and carcass ultrasound prediction

Abstract: The aim of this study was to evaluate the influence of genetic group, sex and level of protein-energy supplementation on the performance and carcass traitsultrasound prediction of weaned calves Nellore and crossbred animals ½ Nellore x ½ Aberdeen Angus. A completely randomized design in a factorial 2x2x2, were used, with two levels of protein-energy supplementation, two sex and two genetic groups. Fifty-six animals were used (28 Nellore and 28 crossbred ½ Nellore x ½ Aberdeen Angus), equally divided between ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…However, it should be considered that the tropical forages hardly present values below the recommended levels when the management and cutting height indicated for the species are adopted (PEREIRA et al, 2011). The results obtained are in agreement with the indications of Pereira et al 2011, Alencar et al (2014), and Guerra et al (2016), who verified that NDF values were always more than 60% in Brazilian pastures formed with different species of Brachiaria. High levels of NDF are a consequence of the proportional decrease in easily digestible molecules, mainly proteins, which play an important role in ruminant nutrition.…”
Section: Chemical Composition Of Morphological Structuressupporting
confidence: 88%
“…However, it should be considered that the tropical forages hardly present values below the recommended levels when the management and cutting height indicated for the species are adopted (PEREIRA et al, 2011). The results obtained are in agreement with the indications of Pereira et al 2011, Alencar et al (2014), and Guerra et al (2016), who verified that NDF values were always more than 60% in Brazilian pastures formed with different species of Brachiaria. High levels of NDF are a consequence of the proportional decrease in easily digestible molecules, mainly proteins, which play an important role in ruminant nutrition.…”
Section: Chemical Composition Of Morphological Structuressupporting
confidence: 88%
“…Neste contexto, Guerra et al (2016) ao trabalharem com suplementação de bovinos a pasto durante o período das chuvas, observaram maior área de olho de lombo para os bovinos que receberam o maior nível de suplementação, corroborando com os resultados desse trabalho. Porém, esses autores consideraram que esse fato estava correlacionado ao maior peso dos animais e ao maior aporte de nutrientes provindos da suplementação, já os animais deste experimento não diferiram no peso final.…”
Section: Discussionunclassified
“…In general, CP supplementation promotes greater performance and, consequently, high body gain and fat deposition rates in grazing cattle (Guerra et al, 2016;Machado et al, 2019;Machado et al, 2020). On the other hand, previous studies have demonstrated that dairy heifers submitted to a high-performance diet, without an adequate nutritional balance between energy and protein may cause damages to the development of the mammary gland due to excessive fat deposition (Weller et al, 2016;Albino et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%